Five‐year outcomes after catheter ablation for atrial fibrillation in patients with hypertrophic cardiomyopathy. (28th January 2020) - Zheng, Shunwen; Jiang, Weifeng; Dai, Jinjie; Li, Kaige; Shi, Hongyu; Wu, Weihua; Liu, Xu; He, Ben; Qiu, Xingbiao; Song, Zhiping
Abstract: Background: Catheter ablation (CA) is a promising option in most patients with refractory atrial fibrillation (AF). However, data on over 5 years' outcomes with larger numbers in hypertrophic cardiomyopathy (HCM) patients with AF have not been reported. We assessed the outcome of 120 HCM patients following CA compared with a non‐CA group and general patients without AF matched by HCM type with a 61.9 ± 31.6‐month follow‐up. Methods and Results: A total of 120 patients (age 61 ± 9.8 years, female n = 43, 35.8%) with paroxysmal AF (n = 60, 50%) and persistent AF (n = 60, 50%) were enrolled. Of the 120 patients, 48 (40%) required redo procedures, and 82 (68.3%) were in sinus rhythm at the last evaluation. The composite clinical events rate following the initial CA was lower than that in the non‐CA group ( P  = .023) and was also comparable to that in general patients without AF matched by HCM type ( P  = .729). Female (HR 2.358, 95% CI, 1.151‐4.831; P  = .019), NYHA functional class III‐IV (HR 2.422, 95% CI, 1.032‐5.685; P  = .042) and left atrial diameter ≥50 mm (HR 3.319, 95% CI, 1.469‐7.499; P  = .004) were predictors of AF recurrence after multiple procedures. Conclusions: CA was successful in restoring long‐term sinus rhythm and improving symptomatic status in most HCM patients with refractory AF especially for those patients with small atrial size and mild symptoms. In addition, CA may contribute to the prevention of major clinical adverse events in the long‐term clinical course.